2023
DOI: 10.1116/6.0002654
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the growth mechanism of aluminide coating on K444 alloy surface by chemical vapor deposition

Abstract: The studies of the growth mechanism of aluminide coatings by chemical vapor deposition (CVD) is an important prerequisite for optimizing the thermal protection properties of aluminide coatings and improving the CVD process parameters; however, the current research on the growth mechanism of CVD aluminide coatings on nickel-based alloys is relatively limited, and there is a lack of systematic studies in this area. In this work, aluminide coatings were prepared on the surface of nickel-based superalloys by the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Recently, some new approaches were reported to increase the operating temperature of NiAl coatings above 1200 °C. These involve the addition of platinum, palladium, zirconium and hafnium [44,46,49,51]. One should mention that the NiAl coatings deposited on MAR 247 exhibited excellent adherence to the base material, as even after the specimen subjected to cyclic loading fractured, no cracks were detected in the area near the fracture (Figure 6a) and the coating was still well connected with the base material (Figure 6b).…”
Section: Gas-phase Depositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, some new approaches were reported to increase the operating temperature of NiAl coatings above 1200 °C. These involve the addition of platinum, palladium, zirconium and hafnium [44,46,49,51]. One should mention that the NiAl coatings deposited on MAR 247 exhibited excellent adherence to the base material, as even after the specimen subjected to cyclic loading fractured, no cracks were detected in the area near the fracture (Figure 6a) and the coating was still well connected with the base material (Figure 6b).…”
Section: Gas-phase Depositionmentioning
confidence: 99%
“…In this process, a precursor gas is introduced into a chamber, where it reacts to form a solid film on the substrate surface (Figure 4). Since CVD is a commonly used process in the industry, the recent advances related to this deposition technique are mainly related to its successful application on different grades of nickel-based superalloys (Table 3) [1][2][3]5,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. It was reported that NiAl coatings were effectively deposited on MAR 247 [1-3,37,39,43,49-51], Inconel 740 [5], Inconel 738 [38,45], Inconel 713 [39,41,52], CMSX 4 [42,44,46], Inconel 100 [39], K-403 [47], K444 [51], pure nickel [48] and even on additively manufactured Haynes 282 [55].…”
Section: Gas-phase Depositionmentioning
confidence: 99%
See 3 more Smart Citations